2019
DOI: 10.1002/cam4.2210
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of pancreatic cancer cell lines with endoscopic ultrasound‐guided biopsy via conditionally reprogrammed cell culture

Abstract: Recent studies have identified the mutational landscape of pancreatic cancer and suggested tumor‐specific subtypes. However, the major hurdle against personalized treatment is the difficulty to obtain sufficient cancer tissues from most inoperable cases. We investigated whether patient‐derived conditionally reprogrammed cells (CRCs) can be constructed using a small piece of tumor tissue using endoscopic ultrasound (EUS)‐guided fine needle biopsy (FNB). Thirty patients with pancreatic solid mass (mean size, 34.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Since there is no study report on the number of cells, grams, milliliters, or size required to successfully culture the preclinical model, we used the number of passes as a criterion to assess the amount of samples required to culture the preclinical model. The study of Lee et al showed that there was no statistically significant difference (87.5 vs. 100%, P = 0.58) between two passes and three passes in acquiring the histological core when used a 20-gauge (G) FNB needle (EchoTip ProCore™ Endoscopic Ultrasound Needle, Cook Medical Inc., Bloomington, IN, USA), both of which could successfully establish the patient-derived cell (PDC) model ( 43 ). In another study, the endoscopists determined the number of passes according to the results of macroscopic on-site evaluation (MOSE), and compared the different success rates of PDAC organoid isolation (P0) and establishment (P5) in cell culture from a single FNB (22-gauge, SharkCore FNB Exchange System, Medtronic Inc., Minneapolis, MN, USA; or Acquire FNB Device, Boston Scientific Inc., Marlborough, MA, USA) pass and a double FNB pass.…”
Section: Characteristics Of Eus-ta Specimens For Establishing Patient...mentioning
confidence: 99%
See 1 more Smart Citation
“…Since there is no study report on the number of cells, grams, milliliters, or size required to successfully culture the preclinical model, we used the number of passes as a criterion to assess the amount of samples required to culture the preclinical model. The study of Lee et al showed that there was no statistically significant difference (87.5 vs. 100%, P = 0.58) between two passes and three passes in acquiring the histological core when used a 20-gauge (G) FNB needle (EchoTip ProCore™ Endoscopic Ultrasound Needle, Cook Medical Inc., Bloomington, IN, USA), both of which could successfully establish the patient-derived cell (PDC) model ( 43 ). In another study, the endoscopists determined the number of passes according to the results of macroscopic on-site evaluation (MOSE), and compared the different success rates of PDAC organoid isolation (P0) and establishment (P5) in cell culture from a single FNB (22-gauge, SharkCore FNB Exchange System, Medtronic Inc., Minneapolis, MN, USA; or Acquire FNB Device, Boston Scientific Inc., Marlborough, MA, USA) pass and a double FNB pass.…”
Section: Characteristics Of Eus-ta Specimens For Establishing Patient...mentioning
confidence: 99%
“…In different models, the success rate in establishing patient-derived preclinical models ranges from 36.4 to 87% ( Table 2 ). Previously, Lee et al showed that the establishment rate of PDC was 36.4% (8/22) using the FNB samples ( 43 ). Hermans et al showed that the engraftment rate of FNB samples (6/10, 60%) was lower than that of surgical samples (4/4, 100%).…”
Section: Characteristics Of Eus-ta Specimens For Establishing Patient...mentioning
confidence: 99%
“…Research by Lee et al (2019Lee et al ( , 2021 showed that CR technology can be used to establish pancreatic cancer cell lines through biopsies guided by endoscopic ultrasound. CRCs from pancreatic cancer tissues have the same genetic characteristics as those from the primary tumor and can be used for genomic research and drug sensitivity studies and can identify new diagnostic and therapeutic targets for pancreatic cancer (Lee et al, 2019(Lee et al, , 2021. The PDX model has become an important tool for translational research, but there are some limitations, including unsustainable in vitro growth.…”
Section: Application In Digestive Diseases Research Modeling Diseasesmentioning
confidence: 99%
“…However, tissue samples can only be obtained from many advanced cancer patients through fine-needle or core needle biopsy. Research by Lee et al (2019 , 2021) showed that CR technology can be used to establish pancreatic cancer cell lines through biopsies guided by endoscopic ultrasound. CRCs from pancreatic cancer tissues have the same genetic characteristics as those from the primary tumor and can be used for genomic research and drug sensitivity studies and can identify new diagnostic and therapeutic targets for pancreatic cancer ( Lee et al, 2019 , 2021 ).…”
Section: Application In Digestive Diseases Researchmentioning
confidence: 99%
“…Conditional reprogramming (CR) is a novel method of co-culturing epithelial cells with irradiated feeder cells in the presence of a Rho-associated coiled-coil kinase (ROCK) inhibitor, which achieves rapid and sustained expansion of primary cancerous and normal epithelial cells [ 8 , 9 ]. These reprogrammed immortalized cells of malignant tumors [ 10 ], such as bladder cancer [ 11 ], prostate cancer [ 12 ], pancreatic cancer [ 13 ], breast carcinoma [ 14 ], and hepatocellular carcinoma [ 15 ], without genetic manipulation or chromosomal abnormalities, represent an adult stem-cell-like state but express fairly low levels of Sox2 , Oct4 , and Klf4 [ 16 ], which are the pluripotent progenitor markers [ 17 ]. What is more, these non-tumorigenic cells can maintain intra-tumor heterogeneity [ 18 ] in addition to keeping their molecular features [ 19 , 20 ], and are only capable of differentiating into the native tissues in which they originated [ 16 , 21 ].…”
Section: Introductionmentioning
confidence: 99%